Restituir os restos, cindir a violência : pela coragem de ver e remontar imagens da ditadura militar - Caroline Cunha Rodrigues (2023)
This research aims to understand the role of images in processes of state violence, considering the context of the Brazilian military dictatorship (1964-1988), and to initiate an analytical exploration of the conditions for the participation of images in gestures of restitution and memory, focusing on the purpose of splitting the violence and returning these images to those who deserve them, to us, to the common place where the construction of memory lies. Starting from Georges Didi-Huberman's ideas and theoretical proposal about surviving images and montage, which are based on Aby Warburg's unfinished Mnemosyne Atlas and Walter Benjamin's thought, we mobilize authors who write about memory, such as Elizabeth Jelin, Leonor Arfuch and Michael Pollak. The guiding thread of an attentive seeing will be constructed through the montage work carried out with former political prisoners and with their relatives. The erratic corpus in spite of all, in Didi-Huberman's terms, was constituted by the location and selection of remnants torn from the Revealed Memories database, maintained by the National Archive, from the remaining documents of the Department of Political and Social Order of Minas Gerais and the Coordination of General Security of Minas Gerais, under the custody of the Public Archive of the State of Minas Gerais, and from the Public Archive of the State of São Paulo. Through interviews with former political prisoners and their families, which correspond to two groups of subjects to whom the gesture of restitution is centrally intended, a reassembly of the surviving images was carried out in order to see and make these images legible. Inspired by Aby Warburg's Atlas, this study aims to create an atlas of survivals and to present contributions to the studies on images of perpetrators and military dictatorships. It is hoped that the adoption of a sensitive strategy will guide us through the theoretical decomposition and the path of making these remnants of images legible in an atlas moved by the critique of violence.